PENGARUH MODEL PROJECT-BASED LEARNING TERHADAP HASIL BELAJAR PADA MATERI KOLOID DI SMK PGRI PONTIANAK - Nurfitriani, Suri; Sahputra, Rachmat; Sartika, Rody Putra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research intended to determine were there any differences the students’ learning result in class XI Audio Visual Technique which was teach with project based learning model then the students class XI Motorcycle Technique which was taught with convensional method and the big effect of the learning project based learning model in koloid material in students’ learning result. The research method used was pre-experimental with planning pretest-posttest control group desigh technique sampling. The sample was the students class XI Audio Visual Technique and class XI Motorcycle Technique.The tools of data collecting were test and interview. The annalysis data used was U-mann Whithey test with α = 5 % was Asymp Sig. (2-tailed) was 0,001, it meant there were differences the students’ learning results wich taught in Project Based Learning then tought in convensional learning in koloid material. The effect was 39,80 % in students’ learning result in koloid material at SMK PGRI Pontianak.Keywords: Project Based Learning, learning activities, and the results of the study.